Platinum(II) Terpyridine Anticancer Complexes Possessing Multiple Mode of DNA Interaction and EGFR Inhibiting Activity - Li, Chaoyang; Xu, Fengmin; Zhao, Yao; Zheng, Wei; Zeng, Wenjuan; Luo, Qun; Wang, Zhaoying; Wu, Kui; Du, Jun; Wang, Fuyi (Frontiers in Chemistry, 2020)
Platinum(II) terpyridine complexes attract increasing attention as they displayed great potential as antitumor agents due to their high intercalation affinity with nucleic acids. Epidermal growth factor receptor (EGFR) is often overexpressed in various tumor cells, leading to uncontrolled growth of tumor, and is regarded as an important target for developing novel antitumor drugs. Herein, we report four platinum(II) terpyridine complexes bearing EGFR inhibiting 4-anilinoquinazoline derivatives as potent multi-targeting antiproliferation agents against a series of cancer cells. EGFR inhibition assay revealed that these complexes are highly potent EGFR inhibitors. But competitive DNA binding assay and docking simulations also suggested that these complexes exhibited multiple mode of DNA interaction especially great affinity towards DNA minor groove. Finally, cellular uptake and distribution measurements by ICP-MS and ToF-SIMS demonstrated that both nucleus DNA and membrane proteins are important targets for their anticancer mechanisms. The complexes herein can therefore be regarded as promising multi-targeting anticancer agents.